Does inward FDI crowd-out domestic investment? evidence from Uganda - Kasule, Twaha Ahmed; Ghani, Gairuzazmi; Mohamad, Noorihsan; Mat Derus, Alias (Elsevier, 2015)
This paper investigates whether Foreign Direct Investment (FDI) crowds-out domestic investment in Uganda. We analyse the effect on the aggregate economy and at sectoral level using data from 1992 to 2012. We obtain a robust neutral effect on the overall economy. At sector level, we find a crowding-out effect in four sectors; a crowding-in effect in two sectors and a neutral effect in three sectors. But generally, results are robust in only six sectors. Finally, an exogeneity test reveals that past economic growth rates do not influence the inflow of FDI, hence there is no endogeneity problem in our analysis.